(untitled) (Altre Modernità, 2022)
This article investigates Alexis Wright’s novel Carpentaria (2006) through the lens of the mimetic theory developed by René Girard, which I combined with Jean Price-Mars’ definition of “collective bovarism” and Umberto Eco’s narrative semiotics. In my close reading of the novel, I explore how the author exposes the detrimental mimetic mechanisms hidden behind characters’ behaviours and relationships to articulate a discourse on the risks of assimilation and the necessity for Aboriginal resistance to neocolonialism. I argue that in Carpentaria the emulation of the dominant society’s values and beliefs by assimilated Indigenous characters results in the social disintegration and vulnerability of the Indigenous communities. Not only do mimetic mechanisms negatively affect the epistemic systems of Aboriginal characters in terms of preparedness to climate change, but they also undermine their social cohesion and physical survival. Furthermore, investigating the text at a semiotic level, I identified some thematic isotopies that Wright uses to emphasise the racial bias and dehumanising attitudes towards black people embedded in the neocolonial gaze. Prioritising the textual dimension of the novel, my approach focuses on how the sociocultural and physical vulnerability of the Indigenous characters is depicted at a philosophical, rhetorical and narratological level. My investigation focuses on four narrative places: the dump, the city, the Pricklebush and the ocean.